If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 9 = x + -23x Reorder the terms: 9 + 5x = x + -23x Combine like terms: x + -23x = -22x 9 + 5x = -22x Solving 9 + 5x = -22x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '22x' to each side of the equation. 9 + 5x + 22x = -22x + 22x Combine like terms: 5x + 22x = 27x 9 + 27x = -22x + 22x Combine like terms: -22x + 22x = 0 9 + 27x = 0 Add '-9' to each side of the equation. 9 + -9 + 27x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 27x = 0 + -9 27x = 0 + -9 Combine like terms: 0 + -9 = -9 27x = -9 Divide each side by '27'. x = -0.3333333333 Simplifying x = -0.3333333333
| 3(-3c-4)-(2c-4)= | | 9c-16=20 | | 7x-27=45+11x | | 325=6+7 | | 2a+6+4a+13= | | x^2+x-6=9-x | | 3x^(3/4)=-24 | | 2t^2-7t-5=0 | | 27/S=9 | | -X^2-11x-25=0 | | 4+3=7y-21 | | 1.5a=1.6a+5 | | 22-3x=-8 | | 2=t/-14 | | 1.25x=8 | | 4r=3(r-2) | | 94=8j+30 | | y=4(x+6)-7 | | x-5/9=8/9 | | 5+4x+5+48= | | -3(t-4)+9t=8t-6 | | 60y^2+3y-36=0 | | x^2=14-7x | | 5(x-8)+26= | | 5x-4(4x-1)=2 | | -6x-142=2x+98 | | 5x+45+9x=180 | | 17=64-n | | i7n/9-62=5n/9-49 | | 31x=56 | | Y/3-4=-2 | | B/5-2=2 |